2019
DOI: 10.3390/molecules24112058
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of a PFOB-Nanoemulsion for 19F Magnetic Resonance Imaging: First Results in Monocytes of Patients with Stable Coronary Artery Disease and ST-Elevation Myocardial Infarction

Abstract: Fluorine-19 magnetic resonance imaging (19F MRI) with intravenously applied perfluorooctyl bromide-nanoemulsions (PFOB-NE) has proven its feasibility to visualize inflammatory processes in experimental disease models. This approach is based on the properties of monocytes/macrophages to ingest PFOB-NE particles enabling specific cell tracking in vivo. However, information on safety (cellular function and viability), mechanism of ingestion and impact of specific disease environment on PFOB-NE uptake is lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Interestingly, 19 F signal changes in remote and infarct/peri-infarct zones yielded similar temporal patterns and trends (fluorine MR signals in MI were highly correlated with macrophage content) 51 , yet the 19 F signal intensities were by far greater in MI compared with remote zones. In contrast, no significant monocyte changes were observed in healthy, acute ST-elevation MI, and stable coronary artery disease patients with PFOB, albeit the reported temporally increasing monocytic trends in these groups for periods up to 6–7 days post-MI 47 .…”
Section: Noninvasive Magnetic Resonance Imaging and Trackingmentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, 19 F signal changes in remote and infarct/peri-infarct zones yielded similar temporal patterns and trends (fluorine MR signals in MI were highly correlated with macrophage content) 51 , yet the 19 F signal intensities were by far greater in MI compared with remote zones. In contrast, no significant monocyte changes were observed in healthy, acute ST-elevation MI, and stable coronary artery disease patients with PFOB, albeit the reported temporally increasing monocytic trends in these groups for periods up to 6–7 days post-MI 47 .…”
Section: Noninvasive Magnetic Resonance Imaging and Trackingmentioning
confidence: 61%
“…Contrary to iron particles in 1 H MRI, fluorinated 19 F NP labels have been introduced as intravenous contrast agents as novel, highly sensitive, exogenously administered 19 F signal beacons (encapsulated by inert/biodegradable polymeric sheaths) given that MR-visible fluorine is absent from endogenous human tissues. The primary constructs include perfluorocarbon ether NPs (PFCE comprising 20 chemically equivalent fluorine atoms with diameters in the range of 85–200 nm 26 , 46 and perfluorooctyl bromide nanoemulsions (PFOB-NE comprising 17 fluorine atoms, diameters of approximately 210 nm 47 ), yet newer clinically applicable constructs (ABL-101) have been reported recently 48 . Despite the relative merits and disadvantages of these label types (MR sensitivity, half-lives, clearance kinetics), they had been used originally in immune therapy 33 , 49 , and myocardial inflammation research studies (PFCE) 50 , 51 but found their ways in clinical trials in colorectal cancer treatments with immunotherapeutic dendritic cell vaccination (PFC) 26 and in inflammation in coronary artery disease (PFOB) 47 .…”
Section: Noninvasive Magnetic Resonance Imaging and Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that PFOB nanodroplets were also utilized as contrast agents for achieving targeted 19 F MR imaging of inflammation [ 428 , 429 ]. The half-life of PFOB was reported to be 12 days and it was reported that it is exhaled through the lung [ 424 , 429 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…The ATHEROMA (Atorvastatin Therapy: Effects on Reduction of Macrophage Activity) study showed a significant reduction in USPIO carotid uptake in patients with carotid stenosis treated with high dose (80 mg/day) of atorvastatin for 12 weeks, indicating a reduction of plaque inflammation, but no effect of a low dose regimen (10 mg/day). 93 Other emerging MR-based techniques, such as fluorine 19 ( 19 F) [94][95][96][97][98] or deuterium 99 MRI are actively being investigated to respectively quantify inflammatory cells or immunometabolism, and have already been used or may show potential applications in CVD. Among other imaging modalities, computed tomography (CT) is currently gaining interest not only for the characterization of vulnerable (soft) plaques, but also for the evaluation of the perivascular fat, whose CT attenuation value has been found to correlate with coronary inflammation by [ 18 F]FDG PET.…”
Section: Multimodality Imaging Of Cardiovascular Inflammationmentioning
confidence: 99%